Do better institutions improve bank efficiency? evidence from a transitional economy - Iftekhar Hasan; Haizhi Wang; Mingming Zhou (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
The pace of transition in China over the last two decades has led to great variation across the country in terms of institutional and financial development. In this paper, using a panel of Chinese provinces during the period 1993-2006, we empirically investigate the determinants of the efficiency of the banking sector from an institutional perspective. The most important institutional developments in China are the emergence and gradual dominance of the market economy, financial deepening, the growth of a private sector, the establishment of secure property rights, and rule of law. We find that institutional variables play an important role in affecting banking efficiencies, and that banks tend to operate more efficiently in those regions with a greater private sector presence and more property rights awareness, while the role of financial deepening and rule of law is less straightforward.
URN:NBN:fi:bof-201408071976
Keywords: G21; O43; 330; Institutional development; Bank efficiency; Chinese banks